Small molecules based difluoroquinoxaline for organic solar cells. Issue 1 (13th October 2021) - Kong, MinSung; Lee, Jihoon; Song, Suhee; Park, Seong Soo; Lee, Won-Ki; Kim, Jin Young; Park, Sung Heum; Jin, Youngeup
Abstract: A new accepter unit, 2, 3-didodecyl-6, 7-difluoroquinoxaline, was prepared and utilized for the synthesis of electron acceptor–donor–acceptor materials for organic solar cells. 2, 3-Didodecyl-6, 7-difluoroquinoxaline unit was designed to introduce electron-withdrawing F atom in quinoxaline unit to improve deeper HOMO energy levels and higher V OC of the materials. The thienothiophene in conjugated materials has more excellent electron-donating ability to decrease of HOMO energy levels, which improves efficiency by increasing the V OC values.